EFFECTIVENESS OF USING EDMODO IN ISLAMIC RELIGIOUS LEARNING ON INCREASING STUDENT DIGITAL LITERACY - Fauzatul Ma'rufah Rohmanurmeta (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe the effect of using Edmodo on Islamic religious learning on increasing student digital literacy. This research is a quasi-experimental research, with a pretest-posttest design with noneequivalent groups. The pretest and posttest are used to measure students' initial and final digital literacy skills before and after Islamic learning activities. The research was conducted on students in the first semester of the Islamic Religious Education course at the University of PGRI Madiun. The research population consisted of 300 students in the fourth semester of the 2021/2022 academic. While the research sample consisted of 60 students consisting of class A and class B. The sample selection was done randomly. Class A is the experimental class, while class B is the control class. The results of the study show that the use of Edmodo in Islamic religious learning is more effective than the use of power point to improve students' digital literacy skills in Islamic cultural history material. It is evident from the results of the t-test with a significance of 0.000 in the experimental group showing that the use of Edmodo has a positive and significant effect on students' digital literacy in Islamic learning.